Seismic Vulnerability in the Himalayan Region - Paudyal, Harihar; Panthi, Ananta (Himalayan Physics, 2011)
The frequently occurring strong earthquakes in the Himalayan region signify the seismic vulnerability in the region. The continued northward movement of Indian plate is generating large amount of stress at the plate boundary which is being released in form of large and great earthquakes (M≥7). Absence of such great events in the Himalayan front for last six decades and in some segments for last two centuries envisages the region as a high potential zone for future seismic hazard. In this paper we studied the larger events in the central Himalayan region.Key words: Central Himalaya; Large earthquakes; Seismic hazardsThe Himalayan Physics Vol.1, No.1, May, 2010Page: 14-17Uploaded Date: 28 July, 2011